1999
DOI: 10.1007/s002130051055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dopamine receptor antagonists on hyperlocomotion induced by cocaine, amphetamine, MK-801 and the dopamine D 1 agonist C-APB in mice

Abstract: The results of the present study suggest that selective blockade of D1 receptors suppresses amphetamine and cocaine-induced hyperactivity in mice but not MK-801-induced locomotor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
3
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 25 publications
10
57
3
3
Order By: Relevance
“…The observations that GS39783, in contrast to baclofen, does not alter baseline locomotor activity is in agreement with the lack of effects in other behavioral tests in both rats and mice, which are sensitive to baclofen administration; these include the rotarod motor coordination task, cognitive tasks, and hypothermia measurements Jacobson and Cryan, 2005). Of note, the effects of GABA B receptor ligands on cocaine-induced hyperactivity appear not as robust as that reported with D1-selective DA receptor antagonists such as SCH23390, which almost completely block the locomotor stimulant effects of cocaine (O'Neill et al, 1999;Adams et al, 2001). However, a thorough evaluation of GABA B receptor-positive modulators in comparison to other drugs attenuating locomotor stimulant effects of cocaine requires sideby-side experiments and a careful investigation of their side-effect profile, which may influence locomotor-based behavioral readouts.…”
Section: Discussionsupporting
confidence: 77%
“…The observations that GS39783, in contrast to baclofen, does not alter baseline locomotor activity is in agreement with the lack of effects in other behavioral tests in both rats and mice, which are sensitive to baclofen administration; these include the rotarod motor coordination task, cognitive tasks, and hypothermia measurements Jacobson and Cryan, 2005). Of note, the effects of GABA B receptor ligands on cocaine-induced hyperactivity appear not as robust as that reported with D1-selective DA receptor antagonists such as SCH23390, which almost completely block the locomotor stimulant effects of cocaine (O'Neill et al, 1999;Adams et al, 2001). However, a thorough evaluation of GABA B receptor-positive modulators in comparison to other drugs attenuating locomotor stimulant effects of cocaine requires sideby-side experiments and a careful investigation of their side-effect profile, which may influence locomotor-based behavioral readouts.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, we observed that the dose-response curve for OLDA was bell-shaped, as are those reported for a number of direct and indirect dopaminergic agents (15)(16). Moreover, it is well documented that hyperactivity induced by both direct and indirect DA agonists is blocked by haloperidol (17)(18)(19)(20), a preferential D 2 receptor antagonist (21)(22). In the present study, haloperidol prevented, in a dose-dependent manner, the OLDA-induced hyperlocomotion, not altering basal locomotor activity in well-habituated animals.…”
Section: Discussionsupporting
confidence: 81%
“…Although neither benzazepine increased horizontal motor activity, others have found increases at doses similar to, or lower than, the lowest dose used in the current experiment (Arnt et al 1992;O'Neill and Shaw 1999). It is possible that the doses used in the current experiment were beyond those that would increase locomotion.…”
Section: Discussionmentioning
confidence: 52%